Pemanfaatan Software Anates Sebagai Evaluasi Butir Soal pada Mata Pelajaran Ekonomi Bisnis dan Administrasi Umum Fase F - Latifa Nurul Hidayati; Luqman Hakim; Vivi Pratiwi; Selvi Agustin; Nabila Aulia Sari; Imro Atus Sholehah; Alfi Rizka Chafidho Hanum; Sarah Fidela Rahayu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to review the quality of test items in Business Economics and General Administration subjects using a classical analysis approach. The assessment process included examining validity, reliability, difficulty level, the ability of questions to differentiate student abilities, and the accuracy of distractors. The research approach used was descriptive quantitative, with 32 students from grades XI and XII majoring in Accounting as subjects and 50 multiple-choice questions as instruments. The main focus of this study was to ensure that the evaluation tools used were truly capable of describing students' competency achievements. Data analysis was conducted through observation results and student responses on Google Forms, which were then processed using the Anates Version 4.0 application. The results of the analysis showed that most of the questions had high validity and reliability, good discrimination power, and a moderate level of difficulty. However, the overall quality of the distractors was not good enough, and there were no questions in the difficult category. Overall, the quality of the questions in this subject can be categorized as good and suitable for evaluating the learning of vocational high school students in grades XI and XII.